Inovasi Mesin Pemipil Jagung Dengan Menggunakan Dinamo Listrik sebagai Sumber Energi Penggerak - Nevita, Ary Permatadeni; Mubarok, Rizqi; Munawi, Hisbulloh Ahlis; Santoso, Rachmad (Universitas Nusantara PGRI Kediri, 2024)
Corn farmers need a corn sheller machine design with a better working principle and effectiveness than the previous machine. The innovation of the corn sheller machine using an electric dynamo as a source of driving energy is a fairly interesting solution to increase efficiency and accuracy in the corn shelling process. The innovation of this corn sheller tool uses the ex - post facto method because the data obtained by researchers is data from events that have already taken place. Researchers only need to develop existing tools and there needs to be development of tools and materials such as sieves, casings, hoppers, exhaust pipes, electric dynamos, exhaust pipes, frames, pulleys, and v-belts. The results and calculations of this tool are, the planned power is 0.186 kw, the planned moment is 64.70 kg/mm, the shear stress is 3.08 kg/mm2, the shaft diameter is 7 mm, the shear stress on the shaft is 0.0806 kg/mm, with an engine speed of 2800 rpm, after the innovation of the tool was tested 3 times, then the average time was 2.5 minutes, with an actual tool capacity of 43.2 kg/hour. Compared to the previous tool, it could only shell around 20 kg/hour. By using an electric dynamo, it is more environmentally friendly, because the sound is not noisy and the use of electricity is not that large, therefore the innovation of this corn sheller machine is very useful for farmers in Slawe Village.Keywords: Farmers, corn shellers, innovation, electric dynamo, shaft